(3TgGH GdCNHGQ aj GdMce hGdCeKGd hGdBOGHs - (3eMeO Hf SdGeI Hf LYaQ Hf Ydj Hf Mcehf GdbVGYj , TgGH GdOjf CHh YHO Gddg,J (B454 (3g` s ((3eMeO Hf SYO GdcGJHi s)
(3ChdgG (B:s
(3CeG HYO aEf ai GdCdaGX GdfHhjI hGdBOGH GdTQYjI LdC dbdhH GdYGQajf hTaGA hbO LeYJ ai cJGHi gPG eG SeYJg ef MOjK QShd Gddg Udi Gddg Ydjg hSde s
(3BNQgG (B:s
(3Gddge Efi CSCdc YjTI ShjI hejJI JbjI heQOkG ZjQ eNR hdG aGVM HQMeJc jG CQMe GdQGMejf Je GdcJGH s
(3GdfSNI HgG MhGTs
(3fSNI Chdis
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B146 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B42 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B71s
Keywords: (3GdMOjK h GdeUWdMs